Politics of occupation-centred practice reflections on occupational engagement across cultures - Pollard, Nick, MSc(OT); Sakellariou, Dikaios (Wiley-Blackwell, 2012)
"Politics of Occupation-Centred Practice addresses the cultural aspects of occupational identity and draws out the implications for practice, moving beyond the clinical environment to include the occupational therapist's work in the wider community"--Provided by publisher.